2022
DOI: 10.1186/s12888-022-04064-1
|View full text |Cite
|
Sign up to set email alerts
|

Social exclusion and mental health among older adults: cross-sectional evidence from a population-based survey in India

Abstract: Background Social exclusion has far-reaching consequences that extend beyond regular activities and access to resources and knowledge; social exclusion is a major social determinant of health. However, there is a lack of evidence on social exclusion and health outcomes among India’s older adults. Thus, the current study investigates the association of social exclusion with depressive symptoms among Indian older adults. Methods This study used infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Yan et al [ 15 ] surveyed 2911 respondents aged 60 and older from the 2018 China Health and Aging Tracking Survey (CHARLS) and found that the prevalence of depression among urban empty nesters was 26.2% and 39.9% among rural empty nesters. Hossain et al [ 24 ] conducted a cross-sectional study of 30,366 respondents aged over 60 years in India and found that depression in older people was 30.3%. A study of the global prevalence of depression in older people found a prevalence of 31.74% [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al [ 15 ] surveyed 2911 respondents aged 60 and older from the 2018 China Health and Aging Tracking Survey (CHARLS) and found that the prevalence of depression among urban empty nesters was 26.2% and 39.9% among rural empty nesters. Hossain et al [ 24 ] conducted a cross-sectional study of 30,366 respondents aged over 60 years in India and found that depression in older people was 30.3%. A study of the global prevalence of depression in older people found a prevalence of 31.74% [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, relationships with friends and their support benefit older people’s well-being (Kail & Carr, 2020). On the other hand, older people living alone and those excluded from social activities have a higher prevalence of depressive symptoms (Hossain et al, 2022). Frequent social contact with children, friends, and relatives has been associated with better adjustment to aging (Rizzuto et al, 2012).…”
Section: Lifestyle Factors and Mental Health In Older Peoplementioning
confidence: 99%
“…According to a meta‐analysis by Zenebe et al, 25 a high global prevalence of depressive symptoms was found among the older population ranging from 7.7% to 81.1%. Multiple factors are associated with geriatric depressive symptoms, such as being female, 26 older age, 27 being single or divorced, 28 lower educational attainment, unemployment, low income, 29 low self‐esteem, 30 loneliness or living alone, 31 social deprivation, 32 presence of chronic illness or poor health status, 33 lack of health insurance, 34 smoking habit, 35 cognitive impairment and a history of depressive symptom 25 . Despite geriatric depressive symptoms being a major problem, they are often undiagnosed, underdiagnosed, undertreated or diagnosed late 36 .…”
Section: Introductionmentioning
confidence: 99%